2014
DOI: 10.1002/jmv.23976
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Sofia Influenza A + B fluorescent immunoassay for the rapid diagnosis of influenza A and B

Abstract: Rapid influenza diagnostic tests (RIDTs) can facilitate the appropriate prescription of antivirals for influenza, obviate the need for unnecessary testing and antibacterial agents and allow the implementation of infection control measures. However, the reported sensitivities and specificities of different RIDTs vary widely in clinical settings, as does assay ability to distinguish between influenza types and subtypes. To evaluate the performance of the Sofia Influenza A + B fluorescent immunoassay (FIA) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
2
15
4
2
Order By: Relevance
“…Our results show that performance of Sofia FIA, above all for sensitivity, is poorer than expected from other studies (Hazelton et al, 2014). Furthermore, rate of false positives is high, in particular for Influenza B.…”
contrasting
confidence: 72%
“…Our results show that performance of Sofia FIA, above all for sensitivity, is poorer than expected from other studies (Hazelton et al, 2014). Furthermore, rate of false positives is high, in particular for Influenza B.…”
contrasting
confidence: 72%
“…Influenza infections are an important cause of morbidity and mortality worldwide in pediatric and adult patients . Early identification of influenza virus as the cause of a respiratory illness is essential for managing patients, facilitating appropriate use of antiviral medications, avoiding unnecessary antibiotic prescriptions, and implementing infection control measures …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Early identification of influenza virus as the cause of a respiratory illness is essential for managing patients, facilitating appropriate use of antiviral medications, avoiding unnecessary antibiotic prescriptions, and implementing infection control measures. 1,2,4,5 Rapid influenza diagnostic tests (RIDTs) are point-of-care tests that detect influenza viral antigens with quick results, usually 30 minutes or less. The Sofia Influenza A+B Fluorescent Immunoassay (Quidel Corporation, San Diego, CA) uses immunofluorescence-based lateral-flow technology to identify viral nucleoprotein antigens in nasal swabs, nasopharyngeal (NP) swabs, and NP aspirates/washes.…”
Section: Introductionmentioning
confidence: 99%
“…Because patients testing positive by Sofia® did not undergo further testing, we could not determine the true sensitivity and specificity of this test compared to FilmArray®. Previous studies have shown Sofia® specificity to be high, with a recent meta-analysis reporting a pooled specificity of 95.3% but sensitivity of only 75.3% for influenza A & B, and pooled specificity of 97.8% and sensitivity of 80% for RSV (Bruning et al, 2017;Gomez et al, 2015;Hazelton et al, 2015;Noh et al, 2015). Similarly, we assumed that all patients testing negative by PCR were true negatives; it is possible that some of these patients could have had false negative tests, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The Sofia® Fluorescent Immunoassay is a rapid, relatively inexpensive lateral flow assay for influenza A and B. It is reported to have a high specificity (94-98.3%) but low sensitivity (72.4-74%) compared to molecular assays (Bruning et al, 2017;Gomez et al, 2015;Hazelton et al, 2015;Noh et al, 2015). It requires less than 5 minutes hands-on setup time and has a 10-15 minute run-time.…”
Section: Laboratory Proceduresmentioning
confidence: 99%